Method for testing OI value of double-layer coated graphite negative electrode

By preparing a double-layer graphite negative electrode piece on the current collector and detecting its OI value on an X-ray diffractometer, the problem of insufficient detection accuracy in the existing technology is solved, achieving higher detection accuracy and consistency, and supporting Research, development and industrialization of double-layer coating technology.

CN119334987APending Publication Date: 2025-01-21安徽国轩新能源汽车科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411508537.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing OI value detection methods cannot accurately detect the OI value of the double-layer coated graphite negative electrode, resulting in insufficient detection accuracy and cannot meet the performance improvement needs of the double-layer coating technology in the field of lithium batteries.

Method used

By preparing a double-layer graphite negative electrode plate coated on one side on the current collector and fixing it on a glass slide on an X-ray diffractometer, the X-ray diffractometer is used to detect the peak intensity ratio of 004/110 of the electrode plate. Ensure that X-rays completely penetrate the double-layer graphite, thereby improving the accuracy and consistency of detection.

Benefits of technology

This method can significantly improve the accuracy and consistency of the OI value detection results of double-layer coated graphite anodes, fills the gap in OI value testing of double-layer coated graphite anodes, and provides a solid foundation to support the research and development of double-layer coating technology. , saving subsequent testing costs and improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119334987A_ABST
    Figure CN119334987A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, in particular to a method for testing the OI value of a double-layer coated graphite negative electrode. The preparation method comprises the following steps: S1, preparing a double-layer graphite negative electrode plate coated on a single surface on a current collector, and carrying out pretreatment processing on the electrode plate; s2, fixing the pre-processed pole piece on a flat surface of a special XRD (X-Ray Diffraction) glass slide on an X-ray diffractometer; s3, X-rays are emitted to the pole piece through an X-ray diffractometer, the pole piece and / or the X-ray diffractometer are / is adjusted through a prediction strategy until a peak appears on the current collector, the 004 / 110 peak intensity ratio of the pole piece is obtained, and the peak intensity ratio is the OI value of graphite in the pole piece. According to the invention, the OI value of the double-layer coated graphite can be accurately detected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium batteries, and in particular to a method for testing the OI value of a double-layer coated graphite negative electrode. Background Art

[0002] With the progress of the times and the development of the lithium battery industry, double-layer coating technology has gradually been applied in the field of lithium batteries. For example, the application of double-sided double-layer coating technology is recorded in the text of Chinese patent publication number CN110335996A, which is titled "A high-capacity lithium-ion battery negative electrode and its application". And the application of single-sided double-layer coating technology is recorded in the text of Chinese patent publication number CN118315523A, which is titled "A negative electrode double-layer coating process, negative electrode sheet and lithium-ion battery". Compared with the traditional single-layer negative electrode process, the double-layer coating negative electrode process can effectively improve the performance of lithium batteries such as rate and energy density.

[0003] After the double-layer graphite coating has different proportions, the OI value of graphite is obviously different, and the impact on battery performance is also different. For research and development, a suitable coating ratio can be inferred through this OI value, so as to better select the raw materials required in the battery, such as the binder, electrolyte, electrolyte additive, etc.; and the OI value can ensure the various indicators of the lithium battery. At the stage of battery raw materials, there is a value to control the battery performance, which saves a lot of subsequent costs and improves efficiency. It plays an important role in studying the various performances and industrialization of lithium batteries.

[0004] Therefore, a method for testing the OI value of a double-layer coated graphite negative electrode with high accuracy and good consistency is of great significance for the development of research and development. However, most of the existing OI value detection methods are only suitable for detecting single-layer graphite materials. For example, as recorded in the text of a graphene-based gas-sensitive material and its preparation method with the Chinese patent publication number CN114014313B, the OI value of the graphene-based gas-sensitive material is: using an XRD diffractometer to test the ratio of the peak area of ​​its 004 characteristic peak to the peak area of ​​its 110 characteristic peak. However, the applicant has found through research that since the OI value detection of a single-layer graphite material does not need to consider the problem of X-ray penetration, when the OI value of a double-layer coated graphite is directly detected using the traditional method of testing the OI value of a graphite material, there is often a problem of insufficient detection accuracy due to the inability to ensure whether the rays penetrate the double-layer graphite, especially for double-sided double-layer coated pole pieces, it is even more impossible to ensure that the rays accurately penetrate all the graphite, and there is a problem of insufficient detection accuracy for double-layer coated graphite pole pieces, which needs to be solved urgently. Summary of the invention

[0005] In order to avoid and overcome the technical problems existing in the prior art, the present invention provides a method for testing the OI value of a double-layer coated graphite negative electrode, which can accurately detect the OI value of the double-layer coated graphite.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for testing the OI value of a double-layer coated graphite negative electrode comprises the following steps:

[0008] S1. preparing a double-layer graphite negative electrode sheet coated on one side on a current collector, and pre-processing the electrode sheet;

[0009] S2, fixing the pre-processed pole piece on the flat surface of the XRD special slide on the X-ray diffractometer;

[0010] S3. X-rays are emitted to the pole piece through an X-ray diffractometer, and the pole piece and / or the X-ray diffractometer are adjusted through a prediction strategy until the current collector peaks, and a peak intensity ratio of 004 / 110 of the pole piece is obtained. The peak intensity ratio is the OI value of the graphite in the pole piece.

[0011] By making a double-layer graphite into a negative electrode sheet on the current collector, and when the OI value is detected by an X-ray diffractometer, by judging whether the current collector has a peak, it can be judged whether the X-ray diffractometer has completely penetrated the double-layer graphite. Compared with directly emitting X-rays to the graphite material through an X-ray diffractometer, which cannot ensure that the X-rays penetrate the double-layer graphite material, the present application makes the negative electrode sheet into a form that has higher consistency and accuracy in the detection results of the OI value of the double-layer graphite; it fills the gap in the OI value test of the double-layer coated graphite negative electrode, and provides a solid foundation for the research and development of this double-layer coating technology.

[0012] As a further solution of the present invention: the prediction strategy in step S3 includes reducing the thickness of the double-layer graphite in the pole piece and / or increasing the irradiation intensity of the X-ray diffractometer; wherein, when the thickness of the pole piece is reduced, the ratio between the double-layer graphite remains unchanged to ensure that the double-layer graphite can be completely penetrated by the X-rays.

[0013] As a further solution of the present invention: whether the current collector in step S3 has a peak is determined by whether the XRD diffraction pattern generated by the X-ray diffractometer has the strongest characteristic peak of the current collector, so as to quickly determine whether the X-ray is traditional double-layer graphite.

[0014] As a further solution of the present invention: the current collector is copper foil, which has the advantages of mature preparation technology and excellent structural stability.

[0015] As a further solution of the present invention: in step S2, the electrode piece is tightly fixed to the XRD glass slide by means of tape to ensure that the electrode piece is flat, thereby ensuring the accuracy of OI value detection.

[0016] As a further solution of the present invention: the incident slit of the X-ray diffractometer is 10mm*10mm, the pure test area on the pole piece of the X-ray diffractometer located outside the tape is larger than 15mm*15mm, and the irradiation area of ​​the X-ray diffractometer points to the pure test area, ensuring that the X-rays can be accurately irradiated in the pure test area.

[0017] As a further solution of the present invention: the pretreatment process in step S1 includes drying, rolling and slitting the electrode piece, and the size of the electrode piece is 20mm*20mm. The size of the electrode piece is appropriate to ensure that the electrode piece is fixed by tape while reserving enough space for the pure test area.

[0018] As a further solution of the present invention: the angle range of the X-ray diffractometer test parameter 2θ is 40-85°, the step size is 0.01°, and the scanning speed is 5-10° / min. Compared with the traditional method of using the peak intensity ratio of 002 / 110 as the graphite OI value, which requires scanning in the range of 10-90°, the scanning time can be greatly shortened and the test efficiency can be improved.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. By making the double-layer graphite into a negative electrode sheet on the current collector, and when the OI value is detected in the X-ray diffractometer, by judging whether the current collector has a peak, it can be judged whether the X-ray diffractometer has completely penetrated the double-layer graphite. Compared with directly emitting X-rays at the graphite material through the X-ray diffractometer, which cannot ensure that the X-rays penetrate the double-layer graphite material, the negative electrode sheet made in this application has higher consistency and accuracy in the detection results of the OI value of the double-layer graphite; it fills the gap in the OI value test of the double-layer coated graphite negative electrode, and provides a solid foundation for the research and development of this double-layer coating technology. In addition, it provides technical support for the subsequent control of the range of OI values, and can determine the quality of battery performance-related indicators at the battery raw material stage, so that there is no need to test the finished battery cells too much during the production process, saving a lot of costs and improving production efficiency. It is of great significance for the study of various performance and industrialization of lithium batteries.

[0021] 2. The electrode is fixed tightly to the XRD slide with tape to ensure the flatness of the electrode and improve the accuracy of the test results.

[0022] 3. The angle range of the X-ray diffractometer test parameter 2θ is 40-85°, the step size is 0.01°, and the scanning speed is 5-10° / min; compared with the traditional method of using the peak intensity ratio of 002 / 110 as the graphite OI value, which requires scanning in the range of 10-90°, it can greatly shorten the scanning time and improve the test efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a flowchart of the workflow of the present invention.

[0024] Figure 2 It is a schematic diagram comparing the cycle performance of batteries made from different samples in Example 3 of the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] For ease of understanding, the specific structure and working mode of the present invention are further described below in conjunction with the accompanying drawings:

[0027] The specific structure of the present invention refers to Figure 1 As shown, the main testing method includes the following steps:

[0028] S1. preparing a double-layer graphite negative electrode sheet coated on one side on a current collector, and pre-processing the electrode sheet;

[0029] S2, fixing the pre-processed pole piece on the flat surface of the XRD special slide on the X-ray diffractometer;

[0030] S3. X-rays are emitted to the pole piece through an X-ray diffractometer, and the pole piece and / or the X-ray diffractometer are adjusted through a prediction strategy until the current collector peaks, and a peak intensity ratio of 004 / 110 of the pole piece is obtained. The peak intensity ratio is the OI value of the graphite in the pole piece.

[0031] In the present application, by making a double-layer graphite into a negative electrode sheet on the current collector, and by judging whether the current collector has a peak when performing OI value detection in an X-ray diffractometer, it is possible to judge whether the X-ray diffractometer has completely penetrated the double-layer graphite. Compared with directly emitting X-rays to the graphite material through an X-ray diffractometer, which cannot ensure that the X-rays penetrate the double-layer graphite material, the present application has higher consistency and accuracy in the detection results of the OI value of the double-layer graphite.

[0032] On the basis of the above, the prediction strategy in step S3 includes adjusting the thickness of the double-layer graphite in the pole piece and / or adjusting the irradiation intensity of the X-ray diffractometer; wherein, when the thickness of the pole piece is adjusted, the ratio between the double-layer graphite remains unchanged. In specific implementation, if the current collector cannot produce a peak during the X-ray irradiation process, the irradiation intensity of the X-ray diffractometer can be increased and / or the overall thickness of the double-layer graphite can be reduced while keeping the ratio of the double-layer graphite unchanged to ensure that the X-rays can penetrate the double-layer graphite.

[0033] Specifically, whether the current collector has a peak in step S3 is determined by whether the strongest characteristic peak of the current collector appears in the XRD diffraction spectrum generated by the X-ray diffractometer.

[0034] Specifically, the current collector is copper foil. Of course, in actual implementation, the current collector can also be aluminum foil or Cu current collector.

[0035] In addition, in step S2, the electrode is fixed tightly to the XRD glass slide by tape to ensure the flatness of the electrode, thereby improving the accuracy of the detection result. The specific effect is demonstrated in Example 1.

[0036] The incident slit of the X-ray diffractometer is 10mm*10mm, the pure test area on the pole piece of the X-ray diffractometer outside the tape is larger than 15mm*15mm, and the irradiation area of ​​the X-ray diffractometer is directed to the pure test area to ensure that the X-rays only hit the 15mm*15mm pure pole piece area.

[0037] The pretreatment includes drying, rolling and slitting the electrode. The size of the electrode is 20mm*20mm. The electrode is of moderate size and space is reserved for tape pasting to ensure that the final pure test area meets the requirements.

[0038] On the basis of the above, the angle range of the X-ray diffractometer test parameter 2θ is 40-85°, the step size is 0.01°, and the scanning speed is 5-10° / min; compared with the traditional method of using the peak intensity ratio of 002 / 110 as the graphite OI value, which requires scanning a range of 10-90°, it can greatly shorten the scanning time and improve the test efficiency. Of course, other parameters except the scanning range can be adjusted according to the different instrument models used to ensure that the complete peak type of the graphite 004 crystal plane and 110 crystal plane can be obtained. In addition, the peak intensity of 004 / 110 is obtained by the PDXL analysis software that comes with the X-ray diffractometer, and other analysis software can also be used instead.

[0039] Example 1

[0040] According to the order of fast-charging graphite, normal graphite and copper foil, two groups of single-sided double-layer coated electrode samples were prepared, named C1 electrode group and C2 electrode group, respectively. There were 10 electrodes in each electrode group, and the ratio of fast-charging graphite to ordinary graphite in each electrode was 5:5. Among them, each electrode in the C1 electrode group was directly placed on the XRD special slide without tape; each electrode in the C2 electrode group was fixed on the XRD special slide with tape according to the above step S2.

[0041] Each electrode in each electrode group is tested separately according to the detection method in the above step S3, and the peak intensity ratio of 004 / 110 in each of the 10 electrode groups in the C1 electrode group and the C2 electrode group is obtained through the XRD analysis software, and the value is the OI value of graphite.

[0042] Specifically, the OI values ​​of the C1 pole piece group and the C2 pole piece group are shown in the following table:

[0043]

[0044] According to the OI value data of the above C1 pole piece group and C2 pole piece group, it can be concluded that the maximum and minimum OI values ​​of the C1 pole piece group without tape are 7.020 and 4.846 respectively, and the range is 2.174; the maximum and minimum OI values ​​of the flat C2 pole piece group with tape are 7.157 and 6.824 respectively, and the range is 0.333; the C2 pole piece group with obvious tape affixed and flattened has a smaller range, more accurate results, and better consistency.

[0045] Example 2

[0046] According to the sequential arrangement order of fast-filling graphite, normal graphite, copper foil, normal graphite and fast-filling graphite, two groups of double-sided double-layer coated pole piece samples were prepared, named C3 pole piece group and C4 pole piece group, respectively, and there were 10 pole pieces in each pole piece group. Among them, in the C3 pole piece group, the ratio of fast-filling graphite to ordinary graphite in the pole piece was 6:4; in the C4 pole piece group, the ratio of fast-filling graphite to ordinary graphite in the pole piece was 5:5.

[0047] According to the order of fast-charging graphite, normal graphite and copper foil, two groups of single-sided double-layer coated pole piece samples were prepared, named C5 pole piece group and C6 pole piece group, respectively, with 10 pole pieces in each pole piece group. Among them, in the C5 pole piece group, the ratio of fast-charging graphite to ordinary graphite in the pole piece is 6:4; in the C6 pole piece group, the ratio of fast-charging graphite to ordinary graphite in the pole piece is 5:5.

[0048] Each electrode is tested individually according to the detection method in the above step S3, and the peak intensity ratio of 004 / 110 in each of the 10 electrode groups in the C3 electrode group, the C4 electrode group, the C5 electrode group and the C6 electrode group is obtained by XRD analysis software, which is the OI value of graphite.

[0049] Specifically, the OI values ​​of the C3 pole piece group, the C4 pole piece group, the C5 pole piece group, and the C6 pole piece group are shown in the following table:

[0050]

[0051]

[0052] The data of the C3 pole piece group, C4 pole piece group, C5 pole piece group and C6 pole piece group are analyzed. It is known that the higher the proportion of fast-charging graphite in the sample, the smaller the graphite OI value. However, from the results of the C3 pole piece group and the C4 pole piece group in the above table, we can see that when using the double-sided double-layer pole piece test, the pole piece OI value of the fast-charging graphite: normal graphite = 6:4 in the C3 pole piece group is larger than the pole piece OI value of the fast-charging graphite: normal graphite = 5:5 in the C4 pole piece group, which is inconsistent with the theory. Through analysis, it is concluded that this may be caused by the X-rays penetrating the copper foil and then penetrating the graphite on the other side, that is, when double-sided double-layer coating is applied, it cannot be guaranteed that the two layers of graphite on the back of the copper foil are completely penetrated after penetrating the copper foil, resulting in different proportions of graphite absorbing different degrees of X-rays. In fact, the measured sample ratio does not match the ratio, causing the OI value to be abnormal. Therefore, for the OI value test of the double-sided double-layer coated pole piece, the method of preparing the single-sided double-layer pole piece in this application is still used for testing, which can ensure that as long as the characteristic peak of the copper foil appears in the test results, it can be said that the X-ray has completely penetrated the fast-charged graphite and the normal graphite. In addition, from the data of the C5 pole piece group and the C6 pole piece group in the above table, we can see that the OI value of the single-sided pole piece with fast-charged graphite: normal graphite = 6:4 in the C5 pole piece group is smaller than the OI value of the single-sided pole piece with fast-charged graphite: normal graphite = 5:5 in the C6 pole piece group, and the result is more accurate. Therefore, it is more accurate to test the OI value using a single-sided double-layer coated pole piece.

[0053] Example 3

[0054] This embodiment aims to provide an application form of OI value detection of double-layer coated pole pieces.

[0055] Specifically, four groups of single-sided double-layer coated pole piece samples were prepared according to the order of fast-charging graphite, normal graphite and copper foil, and they were named A1 pole piece group, A2 pole piece group, A3 pole piece group and A4 pole piece group, and the number of pole pieces in each of the four pole piece groups was 3. Among them, in the A1 pole piece group, the ratio of fast-charging graphite to ordinary graphite in the pole piece was 60:40; in the A2 pole piece group, the ratio of fast-charging graphite to ordinary graphite in the pole piece was 55:45; in the A3 pole piece group, the ratio of fast-charging graphite to ordinary graphite in the pole piece was 50:50; in the A4 pole piece group, the ratio of fast-charging graphite to ordinary graphite in the pole piece was 45:55.

[0056] Each electrode is tested separately according to the detection method in the above step S3, and the peak intensity ratio of 004 / 110 in each of the three electrode groups A1 electrode group, A2 electrode group, A3 electrode group and A4 electrode group is obtained by XRD analysis software, which is the OI value of graphite.

[0057] Specifically, the OI values ​​of the A1 pole piece group, the A2 pole piece group, the A3 pole piece group, and the A4 pole piece group are shown in the following table:

[0058]

[0059] Each electrode in the A1 electrode group, A2 electrode group, A3 electrode group and A4 electrode group is assembled into a battery, and the cycle performance of the battery formed by assembling each electrode in the A1 electrode group, A2 electrode group, A3 electrode group and A4 electrode group is tested respectively. The test results are as follows Figure 2 shown.

[0060] By analyzing the above OI values ​​and the results of sequential performance, it can be found that the closer the ratio of fast-charge graphite to normal graphite is to 50:50, the better the battery cycle performance. Therefore, it can be inferred that the closer the OI value is to 6.749, the more ideal the coating ratio is, and the more conducive it is to battery charging and discharging. Therefore, the determination of the OI value can be used to determine whether some of the battery's performance meets the indicators. In the pole piece production stage, there is a value to control the battery performance, which saves a lot of subsequent costs and improves efficiency.

[0061] Of course, it is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, but also includes the same or similar structures that can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-limiting, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention. Any reference numerals in the claims should not be regarded as limiting the claims involved.

[0062] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0063] The techniques, shapes, and structural parts not described in detail in the present invention are all well-known techniques.

Claims

1. A method for testing the OI value of a double-layer coated graphite negative electrode, characterized in that: The following steps are involved: S1. preparing a double-layer graphite negative electrode sheet coated on one side on a current collector, and pre-processing the electrode sheet; S2, fixing the pre-processed pole piece on the flat surface of the XRD special slide on the X-ray diffractometer; S3. X-rays are emitted to the pole piece through an X-ray diffractometer, and the pole piece and / or the X-ray diffractometer are adjusted through a prediction strategy until the current collector peaks, and a peak intensity ratio of 004 / 110 of the pole piece is obtained. The peak intensity ratio is the OI value of the graphite in the pole piece.

2. A method for testing the OI value of a double-layer coated graphite negative electrode according to claim 1, characterized in that: The prediction strategy in step S3 includes reducing the thickness of the double-layer graphite in the pole piece and / or increasing the irradiation intensity of the X-ray diffractometer; wherein, when the thickness of the pole piece is reduced, the ratio between the double-layer graphite remains unchanged.

3. A method for testing the OI value of a double-layer coated graphite negative electrode according to claim 1, characterized in that: Whether the current collector has a peak in step S3 is determined by whether the strongest characteristic peak of the current collector appears in the XRD diffraction spectrum generated by the X-ray diffractometer.

4. A method for testing the OI value of a double-layer coated graphite negative electrode according to claim 1, 2 or 3, characterized in that: The current collector is copper foil.

5. A method for testing the OI value of a double-layer coated graphite negative electrode according to claim 1, 2 or 3, characterized in that: In step S2, the electrode piece is fixed tightly to the XRD glass slide by means of tape to ensure that the electrode piece is flat.

6. A method for testing the OI value of a double-layer coated graphite negative electrode according to claim 5, characterized in that: The incident slit of the X-ray diffractometer is 10 mm*10 mm, the pure test area on the pole piece of the X-ray diffractometer outside the tape is larger than 15 mm*15 mm, and the irradiation area of ​​the X-ray diffractometer points to the pure test area.

7. A method for testing the OI value of a double-layer coated graphite negative electrode according to claim 5, characterized in that: The pretreatment process in step S1 includes drying, rolling and slitting the electrode pieces, and the size of the electrode pieces cut is 20mm*20mm.

8. A method for testing the OI value of a double-layer coated graphite negative electrode according to claim 1, 2 or 3, characterized in that: The X-ray diffractometer test parameter 2θ has an angle range of 40-85°, a step length of 0.01°, and a scanning speed of 5-10° / min.

Citation Information

Patent Citations

  • High-capacity lithium ion battery negative electrode and application thereof

    CN110335996A

  • A graphene-based gas-sensitive material and its preparation method

    CN114014313B

  • Negative electrode double-layer coating process, negative electrode plate and lithium ion battery

    CN118315523A